2019
DOI: 10.1007/s00004-019-00450-7
|View full text |Cite
|
Sign up to set email alerts
|

Pentagons in Medieval Sources and Architecture

Abstract: A range of entirely different pentagon approximations are known from textual and graphic sources related to the architecture of the Middle Ages. Analysis of the mathematical logic behind them highlights the scientific knowledge of master masons who directly calculated constructional methods according to their practical needs. From the examination of these pentagon approximations, their mathematical features, such as the initial data of the construction or precision of side lengths and angles, the range of arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…The idea originated from the 19th century when several speculative theories were developed concerning medieval design methods (Csemegi, 1953;Fehér and Halmos, 2015;2016). Medieval sources indicate that triangle, square and also pentagon formats (Fehér et al, 2019) were used for plan and detail design, but the logic for these approaches varies widely (Shortell, 2002;Wu, 2002). Without the original plans, any reconstruction of the design cannot exceed hypothesis.…”
Section: Theoretical Background 41 Medieval Design Methodsmentioning
confidence: 99%
“…The idea originated from the 19th century when several speculative theories were developed concerning medieval design methods (Csemegi, 1953;Fehér and Halmos, 2015;2016). Medieval sources indicate that triangle, square and also pentagon formats (Fehér et al, 2019) were used for plan and detail design, but the logic for these approaches varies widely (Shortell, 2002;Wu, 2002). Without the original plans, any reconstruction of the design cannot exceed hypothesis.…”
Section: Theoretical Background 41 Medieval Design Methodsmentioning
confidence: 99%
“…Fehér et al [2] note in an interesting research work on the regular pentagon: "The occurrence of pentagons in medieval architecture tends to be considered as rare; scholars have suggested that its correct geometrical construction was unknown among artists or architects until the early 16th century", but their paper "provides a series of architectural examples containing pentagonal forms highlighting that its role in the design process of medieval masters was much richer than it is currently considered" [2]. "Half decagonal apses, pentagonal traceries, and even design details were related to geometric methods based on the construction of a regular pentagon", which was also used "in plan design of monumental constructions such as the cathedrals of Reims and Saint Quentin" [2].…”
Section: Divine Proportionmentioning
confidence: 99%
“…(Raynaud, 2012) Patrimonio della cultura islamica è un ingegnoso metodo approssimato per disegnare il pentagono. (Fehér, 2019) Il metodo si basa sulla proprietà che la lunghezza dell'arco BC del cerchio ABC è uguale a 2×OA×sin(α/2), dove α è l'angolo centrale ( Fig. 3).…”
Section: Pentagoni Regolari E Approssimatiunclassified